Klasifikasi Kualitas Air Tebu berdasarkan PH dan Warna menggunakan Metode Jaringan Syaraf Tiruan berbasis Arduino - Hafidz Abdillah Masruri; Dahnial Syauqy; Barlian Henryranu Prasetio (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Sugarcane juice (sugar cane juice) is a product of the sugarcane plant (Saccharum officinarum) which can be used as a basic ingredient for making brown sugar, medicine, food, or alcohol. Good sugarcane juice has a pH of 7 to 5 and has a green, brown, yellow color. Sugarcane water have a decrease in quality due to contamination. Decreasing the quality has many impacts such as consumer impacts, benefits impacts, losses, and even be toxic. The parameters that are often used by farmers to determine the quality are color, scent, and taste which sometimes the point of view of a person will be different to determine a fixed standard that can be used. Therefore, the researcher wants to create a system that can fixed parameters, namely the sugarcane water quality classification system with 3 classes: best quality, quality suitable for consumption, and quality not suitable for consumption according to the parameters of sugarcane processing Wajak, Malang City. The system uses a 4502C pH sensor and a TCS3200 color sensor to detect the color and pH of sugarcane juice, then utilizes Arduino UNO as a microcontroller and utilizes PROGMEM syntax so that the memory capacity used can be lighter, the classification process uses the backpropagation artificial neural network method, then the results system is displayed via a 16x2 I2C LCD. Based on the test results, the PROGMEM syntax system was able to get 19% lighter results than without using it and testing 10 samples got 90% accuracy because 9/ 10 tests were successful.